Human Kinematics of Cochlear Implant Surgery: An Investigation of Insertion Micro‐Motions and Speed Limitations. (16th May 2017) - Kesler, Kyle; Dillon, Neal P.; Fichera, Loris; Labadie, Robert F.
Abstract : Objectives: Document human motions associated with cochlear implant electrode insertion at different speeds and determine the lower limit of continuous insertion speed by a human. Study Design: Observational. Setting: Academic medical center. Subjects and Methods: Cochlear implant forceps were coupled to a frame containing reflective fiducials, which enabled optical tracking of the forceps' tip position in real time. Otolaryngologists (n = 14) performed mock electrode insertions at different speeds based on recommendations from the literature: "fast" (96 mm/min), "stable" (as slow as possible without stopping), and "slow" (15 mm/min). For each insertion, the following metrics were calculated from the tracked position data: percentage of time at prescribed speed, percentage of time the surgeon stopped moving forward, and number of direction reversals (ie, going from forward to backward motion). Results: Fast insertion trials resulted in better adherence to the prescribed speed (45.4% of the overall time), no motion interruptions, and no reversals, as compared with slow insertions (18.6% of time at prescribed speed, 15.7% stopped time, and an average of 18.6 reversals per trial). These differences were statistically significant for all metrics ( P <. 01). The metrics for the fast and stable insertions were comparable; however, stable insertions were performed 44% slower on average. The mean stable insertion speed was 52 ± 19.3 mm/min. Conclusion: Results indicate that continuous insertion of a cochlear implant electrode at 15 mm/min is not feasible for human operators. The lower limit of continuous forward insertion is 52 mm/min on average. Guidelines on manual insertion kinematics should consider this practical limit of human motion.